Evaluation of Physical Condition and Mental Ability of Physically Challenged Pupils in Inclusive Education Centres in Jordan - Dr. Reem Abdullah Al-Kenani (Journal of Educational and Human Sciences, 2023)
The study made an evaluation of the physical condition and mental ability of physically challenged pupils in inclusive education centres in Jordan. In order to carry out this study, specified research objectives were formulated and used for the study. The research design for this study is a survey design. The target population for this study included all physically disabled pupils in preschools in Amman, Jordan. A simple random sample was made up of 376 pupils with physical disabilities. The instrument used for data collection was a questionnaire. Data from completed questionnaires was subjected to percentage analysis. The findings demonstrated and conclude that inclusive education development must shift away from a deficit mindset and towards a focus on community collaboration, attention to existing assets, and scaling up successful inclusive education policies and practices. The study recommends that appropriate policies and laws to support inclusive education be made to protect physically challenged pupils against marginalization. that more special education teachers should be employed to cover the deficit and motivate the existing ones.